GLOMUS Camp 2015 in Sarawak, Malaysia - Wee, Roselind (UiTM Sarawak, 2015)
GLOMUS is an international network and initiative for higher education in global music and its related arts. Founded by three Nordic higher education academies of music - the Royal Academy at Music, Aarhus/Aalborg in Denmark, Lund University, Malmo Academy for Music in Sweden and Sibelius Academy in Helsinki, Finland, its aim is to bring forth the vision of creating a sustainable platform that supports and promotes cultural activities as well as the diversity in music performance and education. It is the bridge that connects the global music community across the seven continents, enabling music educators and academies worldwide to share, experience, exchange and educate.